FORUM EKSPERTÓWThe Place of Assist Devices in the Treatment of Heart Failure - Siniawski, Henryk; Dandel, Michael; Weng, Yuguo; Pasic, Miralem; Potapov, Evgenij; Drews, Thorsten; Krabatsch, Thomas; Hetzer, Roland (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Ventricular assist device (VAD) surgery, “surgery” because of the high specificity of the procedure requiring adequate diagnostic possibility and organisation of the surgical and medical team has become an effective and dynamically developed option for treatment of end-stage heart failure (HF). The first implantation of a total artificial heart in a human was done by Cooley on April 4, 1969 in the United States and since that time the dynamic evolution from the concept of saving the lives of patients has converted into optional implantation of VAD. This procedure is not only applied as a last step but also as the treatment of choice when transplantation is not advocated or contraindicated. The Deutsches Herzzentrum Berlin (DHZB) under Professor Hetzer’s supervision and leadership started a VAD surgery programme immediately after the foundation of the institution and a team of specialists is responsible for taking care of these special patients and also caring for them as outpatients. The first implantation of an artificial heart as “Bridge to Transplantation” was done by R. Hetzer in July 1987. Between 04/1986 and 04/2008 a of total 1554 transplantations and 1243 VADs were implanted. The youngest recipient of a VAD was 8 days old and the oldest 71 years old. VAD surgery today incorporates several basic options: 1) assist device as a supporting tool for conservative surgery (reconstructive surgery in the severely diseased heart, heart infarction surgery, coronary bypass surgery, reconstructive surgery in heart infarction complications); 2) supporting options for transplantation programme: a) bridge to transplant, b) bridge to recovery after graft failure, c) bridge to re-transplant after graft failure; 3) independent sector of the assist device programme: a) “Bridge to Recovery” programme; b) permanent non-biological cardiac replacement (destination therapy); 4) paediatric assist device programme. Paediatric surgery was established and developed in DHZB and continues to receive special attention as the results are very good and spontaneous recovery in children can be achieved in a substantial number of cases. This is a very encouraging message for the future of independent use of VADs which we also observe in adults. Currently the DHZB has 36 surviving patients with idiopathic dilated cardiomyopathy among 83 patients weaned from VADs since 3/1995 after an average of 333 days of support. The figure for post-weaning 10-year survival with native hearts has reached 70.7±9.2%, which is better than the life expectancy after heart transplantation. Including post-transplant survival for patients with recurrent heart failure (successfully transplanted patients) the overall 5- and 10-year survival is even better than transplantation and reaches 79.1 and 75.3% respectively. There are several diseases in infants and adults that are potentially treatable surgically on the basis of a VAD or when a “stand-by” assist device is taken into account. This is promising news when VAD surgery is reaching a higher standard on the basis of new technological developments. Regardless of the highly developed technologies and standards, the human aspect should rank first.